PENGARUH TIME BUDGET PRESSURE, INTEGRITAS, OBJEKTIVITAS DAN PENGALAMAN KERJA TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITORSEBAGAI VARIABEL MODERASI - Ryan, Azano; Yuneita, Anisma; Al, A Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to determine the effect of time budget pressure, integrity, objectivityand work experience on audit quality with audit ethics as a moderating variable. So inthis study the population used was an independent auditor who worked at the PublicAccounting Firm (KAP) in Medan, Batam, Padang and Pekanbaru. The samplingtechnique uses purposive sampling method. So the sample in this study was 90 people.The type of data used in this study is quantitative data in the form of secondary data withcollection techniques in documentation from existing data. This study was tested usingmultiple regression analysis with the help of processed statistical data with SPSS version21. The classic assumption test used was multicollinearity test, heterocedasticity test andautocorrelation test. The hypothesis test used is the statistical t test and the coefficient ofdetermination test. The results of hypothesis testing indicate that there is a significanteffect between Time Budget Pressure, Integrity, Objectivity, Work Experience that has asignificant effect on Audit Quality. There is a significant influence between Time BudgetPressure and Auditor Ethics, Integrity and Auditor Ethics, Objectivity and Auditor Ethics,Work Experience and Auditor Ethics have a significant effect on Audit Quality.Keyword: Time Budget Pressure, Integrity, Objectivity, Work Experience, Audit Quality,Auditor Ethics